FutureProbe: imagining possibilities, creating opportunities. - McGuinness, Kevin (Futurist)
More than 800 people gathered in Atlanta, Georgia, on July 18-20 for the World Future Society's annual conference, “FutureProbe: Imagining Possibilities, Creating Opportunities.” The conference included discussions of the cities of the future, the impact of information technology on the Olympic Games, the implications of the research revolution in the biological fields, artificial life research, teachers and technology, and how war and terrorism will be targeted at control of information.